1998
DOI: 10.1021/la970916s
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy and X-ray Reflectivity Studies of Albumin Adsorbed onto Self-Assembled Monolayers of Hexadecyltrichlorosilane

Abstract: Atomic force microscopy (AFM) and X-ray reflectivity (XR) have been used together to provide a detailed and direct look at the structure of human serum albumin protein adsorbed onto well-characterized selfassembled monolayer (SAM) surfaces at several protein concentrations. The duration of SAM deposition was also varied to investigate the influence of the density of hydrocarbon chains in the SAM on protein binding tenacity. Concurrent study of adsorption to bare silicon wafers with native oxide surfaces provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
126
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(148 citation statements)
references
References 35 publications
22
126
0
Order By: Relevance
“…Films prepared with TESP generally had more aggregates present on the surface compared to the OTMS films. Water contact angle measurements of the OTMS and TESP films ( Table 2) are consistent with SAMs prepared from octadecyltrichlorosilane and a 4 -6mer oligoethylene glycol grafted silane, respectively (19,22,26). …”
Section: Sam Preparation and Characterizationsupporting
confidence: 67%
See 2 more Smart Citations
“…Films prepared with TESP generally had more aggregates present on the surface compared to the OTMS films. Water contact angle measurements of the OTMS and TESP films ( Table 2) are consistent with SAMs prepared from octadecyltrichlorosilane and a 4 -6mer oligoethylene glycol grafted silane, respectively (19,22,26). …”
Section: Sam Preparation and Characterizationsupporting
confidence: 67%
“…The concentration of BSA is similar to the concentration of proteins in cell culture sera (~6 mg/mL), which in turn is near physiological protein concentrations (~40 mg/mL). Protein adhesion studies found in the literature (23,24,26,27,29) have typically used concentrations between 1.0 -0.01 mg/mL, which is the concentration range where the protein-surface adsorption isotherm rise is steepest. By employing concentrations at which the adsorption isotherm has the steepest slope, the effect of surface passivation is more distinct.…”
Section: Bsa Adsorption On Sam Coated Siliconmentioning
confidence: 99%
See 1 more Smart Citation
“…From the XRR evaluation and CAH, discussed in the next section, layers formed from 15 to 45 min were very difficult to distinguish. Previous XRR studies of silane showed thickness of 2.1 +/ 0.3 nm with a densities ranging from 0.76 -0.87 g/cm 2 for complete monolayer formation [145], [146], consistent with what we observe. Higher densities were shown to correspond to incomplete SAM formations [146].…”
Section: Sam Formationsupporting
confidence: 92%
“…Previous XRR studies of silane showed thickness of 2.1 +/ 0.3 nm with a densities ranging from 0.76 -0.87 g/cm 2 for complete monolayer formation [145], [146], consistent with what we observe. Higher densities were shown to correspond to incomplete SAM formations [146]. Additionally, the AFM scan of the anodized tantalum oxide substrate showed a RMS roughness of 0.612 nm, the same as found from the XRR measurement.…”
Section: Sam Formationsupporting
confidence: 92%